Fetal intracranial hemorrhage related to maternal autoimmune thrombocytopenic purpura - KORKMAZ, LEVENT; Kütük, Mehmet serdar; Croisille, Leo; GÖRKEM, SÜREYYA BURCU; YILMAZ, EBRU; Korkmaz, Levent; Bierling, Philippe; ÜNAL, EKREM (My University, 2014)
Background Maternal autoimmune thrombocytopenic purpura (AITP) can cause fetal intracranial hemorrhage.